Exploring phage diversity and potential: Development of phage therapy for bacterial infection - Ira Aryani Wirjon; Yahya Mat Arip (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The recent increase in drug-resistance bacteria has become a very serious threat to the treatment of infectious diseases. Over recent decades, a growing numbers of literatures have validated the application of bacteriophages for therapy against antibiotic-resistance bacteria. With rapid dissemination of these resistant bacteria pathogens, the interest in alternative remedies to antibiotics using bacteriophages therapy is gaining new ground. Based on the recent studies of bacteriophage applications against bacterial infections in countries where this alternative therapy has been approved, many scientists and companies believed that phages have the ability to treat and prevent diseases caused by bacteria. Malaysia, being well known as one of the mega diverse countries could promise the potential new phages that could be applied in phage therapy. The overall objectives of this research including isolation and purification of potentially new phages from environments, characterization of the isolated phages based on morphological study, physicochemical attributes, genomic and proteomic analysis. Lastly, the isolated phages would be developed into phage therapy against bacterial infection through in vitro and in vivo test. Preliminary results presented here, show a total of four phages were successfully isolated from human waste. Two of the phages were successfully isolated infecting Proteus mirabilis that caused urinary tract infection in human whereas another two phages infecting Escherichia coli 0157:H7 (caused food-borne diseases) and Escherichia coli ATCC 13706, respectively.